Relationship between the autoantibody and expression of β3-adrenoceptor in lung and heart. - Guobin Miao; Zhe Chen; Xiangyang Fang; Miaobing Liu; Gang Hao; Huiling An; Zhiyong Zhang; Lingqiao Lu; Jian Zhang; Lin Zhang (PLoS ONE)
Background Evidences suggest that β3 -adrenoceptor (β3-AR) plays an important role in heart failure (HF), although no data is reported indicating how these effects may change with the increasing age. Pulmonary congestion and edema are the major life-threatening complications associated with HF. The purpose of this study is to explore the relationship between the anti-β3-AR autoantibody and the expression of β3-AR in the lungs and heart for both aged patients and rats with HF. Methods Synthetic β3-AR peptides served as the target antigens in ELISA were used to screen the anti-β3-AR autoantibody in aged patients and rats. Two aged rat models were constructed based on aortic banding and sham-operation. The expression of β3-AR mRNA and protein in the lung and heart was measured in intervention and non-intervention groups by Western blot analysis at the baseline, 5(th), 7(th), 9(th) and 11(th) week, respectively. Results The frequency and titer of anti-β3-AR autoantibody in aged patients and rats with HF were higher than those in the control group (p<0.05). The expression of β3-AR mRNA and protein in pulmonary tissues decreased continually from the 7(th) week (p<0.05), followed by HF observed during the 9(th) week. The expression of β3-AR in myocardial tissues continued to increase after the 9(th) week (p<0.05), and the expression of both β3-AR mRNA and protein in the BRL group [HF group with BRL37344 (4-[-[2-hydroxy-(3-chlorophenyl)ethyl-amino] phenoxyacetic acid) (a β3-AR agonist) injection] was positively correlated with BRL37344 when compared with non-BRL group (HF group without BRL37344 injection) (p<0.05). Conclusion Anti-β3-AR autoantibody was detected in aged patients and rats with HF. The expression of β3-AR mRNA and protein in pulmonary tissues decreased continually, and began earlier than in the heart, but its expression in myocardial tissues increased continually and could be further promoted by β3-AR agonist.